Clinical Comparison of Ibuprofen Drug Effect and Low Power Laser Diode on Orthodontic Separator Implementation Pain - Mollabashi, Vahid; Maleki, Elham; Rezaei-Soufi, Loghman; Soheilifar, Sepideh; Amini, Payam; Kazemisaleh, Azadeh (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: Placing orthodontic separators is one of the common tasks in orthodontics. It can cause low to moderate pain, because of the pressure of the periodontal ligament and the release of prostaglandins. The purpose of this study was to compare the analgesic effects of Ibuprofen® 400mg (Gelophen, Zahravi Pharmaceutical Co, Tabriz, Iran) and LLLT on pain after the placement of orthodontics separator. Material and Methods: In this randomized clinical trial study, 61 orthodontics patients were randomly divided into two groups: group one LLLT (31 patients) and group two Ibuprofen drug (30 patients). The age of the patients was 13 to 25 years old. After obtaining informed consent from the patients, Maxillary first molars were selected to place separators in mesial and distal contacts. Results: After receiving the questionnaires, 11 patients (6 patients from the laser group and 5 patients from drug group) due to the taking of another medication during the study period, were set aside. Data from 50 of them were analyzed. Using the Chi-square test, no difference was seen between two groups base on the amount of pain experienced, time to start pain and other causes of pain. Only in the drug group initiation of pain was observed later than the laser group. Conclusion: As there was no difference in pain experienced between the two groups according to cost and time, it is not preferable to use low-power laser compared to medicine. The drug seems to be more effective.